Density - Claire Harper (Footprint)
The publication of the planning agenda Towards an Urban Renaissance in 1999 marked a turning point in the approach towards urban development in the UK and specifically towards urban density. Density was attributed with a range of physical, environmental and social implications, or at least potentialities. Most significant of these was the association of high urban densities with more sustainable, socially diverse, compact urban models – a positive affiliation that lead to the introduction of minimum density ratios for new urban developments and the gradual introduction of density ratios as a component of development briefs for new urban housing.